PSYCHOLOGIST'S PROFESSIONAL SECRECY VERSUS SECRECY IN CRIMINAL PROCEEDINGS - Konrad Burdziak; Magdalena Kowalewska-Łukuć (Probacja, 2023)
The aim of this paper is to give an adequate answer to the question of the status of information obtained by a psychologist in the course of his/her profession. This answer is closely related to the examination of whether such information constitutes a secret within the meaning of the Code of Criminal Procedure and whether it is a "professional secret", as referred to in Article 180 1 of the Code of Criminal Procedure, or a "medical secret", as referred to in Article 180 2 of the Code of Criminal Procedure. In order to examine these issues, the authors have used the analysis of normative material relating to the issue under examination, primarily the Act of 6 June 1997 - the Code of Criminal Procedure; and the analysis of the views of the doctrine of criminal law. The considerations contained in this paper, which illuminate the issue of professional secrecy of a psychologist, including also, or perhaps above all, its importance and relevance to practising this profession reliably and responsibly, lead to the conclusion that it is necessary to equate professional secrecy of a psychologist with medical secrecy.